Coherence Aspects Within Efl Essay - erna megawati (Scope : Journal of English Language Teaching, 2019)
The purpose of this research is to discover Indonesian undergraduate students’ understanding in composing a coherence English essay. The subjects of the research are essay texts written by thirty undergraduate students using theme “Students’ attitude toward Indonesian language” chosen randomly. The analysis has revealed that s coherence aspects have not used properly, more over there is one aspect is not used. The coherence aspects consist of repetition key noun, using consistent pronoun, transition signals and logical order. This research is designed as library research using content analysis method. Data are analyzed to investigated the coherency in students’ essay.Key words: essay, coherence